Implementing Active Offer of Services in Both Official Languages in a Hospital Setting in Ontario - Sauvé-Schenk, Katrine; Savard, Jacinthe; Durand, François (Healthcare Policy, 2024)
Providing services in a patient's preferred language is linked to safe and quality care. This paper presents the process and outcomes of implementing practices of active offer (AO) of French-language services in a hospital setting in a region of Ontario with a low density of francophones. Participating unit managers and site coordinators selected AO practices and carried out an implementation plan. The implementation's success was linked to the support received from higher management and site coordinators. Challenges included the managers' rival priorities and perceived language priorities. This process could be applied to meet the needs of other language communities.

L’accès aux services en français, de la connaissance des défis à l’accompagnement des organisations vers le changement. - Savard, Sébastien; Savard, Jacinthe; Sauvé-Schenk, Katrine; van Kemenade, Solange; Benoît, Josée (Minorités linguistiques et société, 2024)
Depuis 2011, le Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire (GReFoPS) cherche à mieux comprendre les facilitateurs et les obstacles à l’offre de services en français dans un contexte linguistique minoritaire au Canada. Dans cet article, les auteurs présentent un bilan de près de 12 ans de recherche sur le sujet, en décrivant les facteurs individuels et organisationnels qui influencent l’offre de services en français. Les résultats de ces études ont mis en lumière quelques mécanismes organisationnels ou interorganisationnels qui ont permis l’émergence de pratiques novatrices pour améliorer l’offre de services en français dans les services communautaires et institutionnels. On y décrit également des outils créés pour aider les gestionnaires de ces services à identifier des mesures et des mécanismes pouvant répondre aux besoins des usagers francophones en situation minoritaire. Mots-clés : accès, services sociaux et de santé, francophones, contexte minoritaire, Canada

Implementation of Innovative Strategies to Increase French Language Services in Three Canadian Health and Social Services Organizations. Research report, - Savard, Sébastien; Savard, Jacinthe; Benoît, Josée; Sauvé-Schenk, Katrine; de Moissac, Danielle; Durand, François; Dupuis-Blanchard, Suzanne (2024)
fs-ref-orig: Savard, S., Savard, J., Benoît, J., Sauvé-Schenk, K., de Moissac, D., Durand, F., Dupuis-Blanchard, S. (2024). Implementation of Innovative Strategies to Increase French Language Services in Three Canadian Health and Social Services Organizations. Research report, Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire (GReFoPS), Université d'Ottawa. fs-code-orig: Savard-2024d